Competencias para el cierre de brechas en emprendimiento de base tecnológica en universidades con escasa trayectoria: perspectiva de expertos colombianos - Benavides-Sanchez, Edward-Andrés; Castro-Ruíz, Camilo-Andrés; Quintero-Ángel, Mauricio (Revista Científica, 2023)
Currently, university-based technological entrepreneurship (EBT) is regarded as a key factor for the development of new high-impact products and services. However, due to the fast-paced dynamics of the market, the competencies necessary for a successful EBT quickly become obsolete. Additionally, there is no specific competency framework for the Latin American context. Therefore, the objective of this article is to establish the competencies required in EBT training processes at universities with little experience in entrepreneurship. To this effect, an inquiry was carried out with Colombian experts linked to entrepreneurship institutions and programs, in which they were asked about the knowledge, skills, qualities, methodologies, and didactics necessary for the emergence of EBT. The results highlighted the importance of entrepreneurship as an institutional priority, understood as a transversality and not limited only to business or economic disciplines. Likewise, it was pointed out that universities with little experience in entrepreneurial training should adopt a competency-based training, which implies the implementation of dynamic pedagogical strategies focused on experience, self-awareness, and practical action, in order to ensure that students are actively involved in the learning process.